2021
DOI: 10.1093/arclin/acab056
|View full text |Cite
|
Sign up to set email alerts
|

Verbal Fluency Tasks: Influence of Age, Gender, and Education and Normative Data for the Spanish Native Adult Population

Abstract: Objective: Phonological and semantic verbal fluency (VF) tasks are frequently used to assess language and executive functions in both clinical and research settings. F, A, and S are the most commonly used letters in phonological tasks across languages and cultures. Unfortunately, the lack of norms for the native Spanish population for these letters, and for certain semantic categories such as “proper names,” may lead to misinterpretation of scores due to demographic differences. The aim of the present study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
1
8
0
Order By: Relevance
“…Over the past few decades, a range of studies have presented normative data for phonemic fluency in general populations, using trials with either single or triple letters [29,37,38,47,[50][51][52][53][54][55][56][57][58][59][60]. These studies have been conducted across various countries, including the U.S. [29,37,38], Canada [47,53], Brazil [52,55], Spain [56], France [58], Greece [54], Italy [51], Iceland [59], Ireland [60], and so forth [50,57,58]. However, most of these studies have recruited rela-tively small sample sizes, typically involving fewer than 500 individuals [38,[51][52][53][54][55][56][57]61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the past few decades, a range of studies have presented normative data for phonemic fluency in general populations, using trials with either single or triple letters [29,37,38,47,[50][51][52][53][54][55][56][57][58][59][60]. These studies have been conducted across various countries, including the U.S. [29,37,38], Canada [47,53], Brazil [52,55], Spain [56], France [58], Greece [54], Italy [51], Iceland [59], Ireland [60], and so forth [50,57,58]. However, most of these studies have recruited rela-tively small sample sizes, typically involving fewer than 500 individuals [38,[51][52][53][54][55][56][57]61].…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been conducted across various countries, including the U.S. [29,37,38], Canada [47,53], Brazil [52,55], Spain [56], France [58], Greece [54], Italy [51], Iceland [59], Ireland [60], and so forth [50,57,58]. However, most of these studies have recruited rela-tively small sample sizes, typically involving fewer than 500 individuals [38,[51][52][53][54][55][56][57]61]. This limitation has potentially impeded the development of norms specific to different demographic groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have found the different effects of age when comparing semantic fluency (SF) and PF (Santos Nogueira et al, 2016;Tombaugh et al, 1999), whereas others did not (Khalil, 2010;Loonstra et al, 2001). However, the impact of the educational level on the performance of VF tasks has been widely recognized in neuropsychological research (Lubrini et al, 2022;Peña-Casanova et al, 2009). It has been found that higher education levels are associated with the production of more words (Oberg & Ramírez, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous initiatives have provided norms for phonological fluency (PF) tests in different populations of Spanish-speaking natives from Spain: Peña-Casanova et al, (2009) for community-dwelling cognitively normal adults ( n = 346), ranging from 50 to 94 years of age, used the letters P, M, and R; Casals-Coll et al (2013) for a younger population, adults between 18 and 49 years old ( n = 179), used the letters P, M, and R; and Lubrini et al (2022) that assessed participants from 17 to 100 years old ( n = 257), utilized the letters F, A, and S. If we consider what has been mentioned before about the choice of reference normative data, it is evident that the studies carried out with a small sample (Casal-Coll et al, and Lubrini et al) would be the first to discard. Considering the date of publication, the work by Peña-Casanova et al, is 14 years old, so it could be considered outdated.…”
Section: Introductionmentioning
confidence: 99%